2021
DOI: 10.1115/1.4049656
|View full text |Cite
|
Sign up to set email alerts
|

Design Ideation Through Speculative Fiction: Foundational Principles and Exploratory Study

Abstract: The objective of this work is to position speculative fiction as a broader framework to stimulate, facilitate, and study engineering design ideation. For this, we first present a comprehensive and detailed review of the literature on how fiction, especially science fiction, has played a role in design and decision-making. To further strengthen the need for speculative fiction for idea stimulation, we further prototype and study a prototype workflow that utilizes excerpts from speculative fiction books as textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…To answer these questions, we designed two experiments based on a previous study completed in 2021 (Xu et al 2021). Researchers have explored the potential of leveraging science fiction narratives to enhance designers' ideation processes (Sterling 2005;Bleecker 2009;Dunne and Raby 2013;Callaghan 2015;Kotecha et al 2021). However, to fully incorporate science fiction into design, we must deal with the time-consuming and labour-intensive task of collecting and verifying speculative technologies from science fiction narratives.…”
Section: Methodsmentioning
confidence: 99%
“…To answer these questions, we designed two experiments based on a previous study completed in 2021 (Xu et al 2021). Researchers have explored the potential of leveraging science fiction narratives to enhance designers' ideation processes (Sterling 2005;Bleecker 2009;Dunne and Raby 2013;Callaghan 2015;Kotecha et al 2021). However, to fully incorporate science fiction into design, we must deal with the time-consuming and labour-intensive task of collecting and verifying speculative technologies from science fiction narratives.…”
Section: Methodsmentioning
confidence: 99%
“…Science fiction fosters creativity and imagination; it allows the audience to envision both the scientific present and future absent the shackles of feasibility (Kotecha et al, 2021). Love and Fox (2021) describe science fiction as engaging readers in “social dreaming,” in which they can imagine various scenarios of positive and negative societies and contemplate social change.…”
Section: Introductionmentioning
confidence: 99%
“…Anguera and Gazzaly 9 concluded that cognitive abilities can be enhanced through video games, which in-turn help in mastering multitasking, goal management and overcoming difficulty levels in performing any task. Apart from video games, the design ideation based on the works of speculative fiction 10 provides a platform for learning and improving the design skills through creativity.…”
Section: Introductionmentioning
confidence: 99%